Existential novel, philosophical narrative - Jiménez, Mauro (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
This paper deals with the relation between literature and philosophy within existentialist thought. This relation is studied in the narrative field and in what is called 'the existential novel'. An analysis of the main characteristics of this kind of narrative demonstrates why literature is a privileged medium of expression for existentialism. The methodological perspective of Comparative Literature is used in this analysis.
Keywords: existential novel; philosophical novel; philosophical literatura; Comparative Literature; existentialism